2015
DOI: 10.1016/j.bfopcu.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, molecular docking and anticonvulsant evaluation of novel 6-iodo-2-phenyl-3-substituted-quinazolin-4(3H)-ones

Abstract: A new series of 6-iodo-2-phenyl-3-substituted-quinazolin-4(3H)-one (5-12 a-b ) derivatives were synthesized, evaluated for their anticonvulsant activity against pentylenetetrazole (PTZ)-induced seizures and maximal electroshock test and compared with the reference drugs phenobarbital sodium and methaqualone. The neurotoxicity was assessed using rotarod test. The molecular docking was performed for all the synthesized compounds to assess their binding affinities to GABA-A receptor in order to rationalize their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The small‐molecules and protein were minimized using the OPLS 2005 force field. The default settings in Glide Docking were used to generate grid considering the active site residues as explored by Ibrahim et al and Abulkhair et al to define the center of the grid box (20 Å × 20 Å × 20 Å). Prepared small molecules were docked into the protein structure using Glide 6.3 XP docking .…”
Section: Methodsmentioning
confidence: 99%
“…The small‐molecules and protein were minimized using the OPLS 2005 force field. The default settings in Glide Docking were used to generate grid considering the active site residues as explored by Ibrahim et al and Abulkhair et al to define the center of the grid box (20 Å × 20 Å × 20 Å). Prepared small molecules were docked into the protein structure using Glide 6.3 XP docking .…”
Section: Methodsmentioning
confidence: 99%
“…Unlike Compound IIIg, Compound IIIh showed moderate protection at 3o min and 4 hr in maximum electro shock seizure which is due to the presence of amine group at the 3 rd position of quinazoline ring. The amine group is an electron donor and increases the hydrogen bonding interaction with the target proteins or receptor for better CNS activity [22]. Finally, it may be concluded that IIc, IIg, IIj, IIIg, IIIh displayed better activity profiles compared with other derivatives as anti-convulsants with a sustained action.…”
Section: Anticonvulsant Activitymentioning
confidence: 97%
“…Some of the potent anticonvulsants with quinazolinone nucleus are depicted in Figure . The substitution of quinazolinone by electron withdrawing halogens at 6 th , 7 th or 8 th positions resulted derivatives with optimum anticonvulsant activity and lower toxicity than phenytoin . Ralitoline is a recently reported AED, found effective in both MES and kindling models of seizures with rodents .…”
Section: Introductionmentioning
confidence: 99%
“…First objective was based on a postulate that aryl ring at second position of quinazolinone is not always necessary for anticonvulsant activity . Second objective was to replace 6,7‐dimethoxy group by using electron withdrawing chlorine atom at 7 th position of quinazolin‐4(3 H )‐one nucleus to enhance anticonvulsant activity with improved side effect profile . In continuation of our research to find novel anticonvulsants with significantly improved therapeutic profile, here we have reported structurally optimized novel 7‐chloroquinazolino‐phenylacetamides by molecular fragmentation approach.…”
Section: Introductionmentioning
confidence: 99%